PERANAN KOMUNIKASI DALAM KELUARGA TERHADAP PEMBENTUKAN JATI DIRI REMAJA - Hasibuan, Effiati Juliana (PERSPEKTIF, 2012)
One of the biggest challenges of adolescence is constructing their self-identity. Teens between the ages of 13 and 21 are not only maturing physically, but they are also growing into their new role as adults. In order to do this, they need to answer for themselves the question "Who am I?" In traditional or particularly rigid communities or families, the young person may have very limited choices in who or what they become. This stage can often involve at least some delinquency, rebellion or acting-out of negative behaviors, and it will probably always include identity crisis and instabilation emotion. However, toward the end of this period, the young adult has usually settled on a clear and positive role for theirself. In maturity process, adolescents want to differentiate themselves from the others. They deliberately choose to be different and make different choices. Along with this, they begin to turn to their peers and friends, rather than their family, for their social and emotional needs. Peer pressure becomes a powerful force and, whether for good or bad, it can have a major impact on their behavior. However, to successfully pass this turning point, they must begin to define ideals and beliefs that will guide them to have a clear picture of how they want their lives to be. The role of communication in family becomes very important to guide the adolescent tobe a good young man with a good self-identity too.